Search for New T' particles in final states with large jet multiplicities and missing transverse energy in p p collisions at sqrt[s] = 1.96 TeV. - Aaltonen, T; Álvarez González, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Appel, J; Apresyan, A; Arisawa, T; Artikov, A; et al. (2011)
We present a search for a new particle T' decaying to a top quark via T' → t + X, where X goes undetected. We use a data sample corresponding to 5.7 fb(-1) of integrated luminosity of p p collisions with sqrt[s] = 1.96 TeV, collected at Fermilab Tevatron by the CDF II detector. Our search for pair production of T' is focused on the hadronic decay channel, pp → T'T' → tt + XX → bqq b qq + XX. We interpret our results in terms of a model where T' is an exotic fourth generation quark and X is a dark matter particle. The data are consistent with standard model expectations. We set a limit on the generic production of T'T' → tt + XX, excluding the fourth generation exotic quarks T' at 95% confidence level up to m(T') = 400 GeV/c(2) for m(X) ≤ 70 GeV/c(2).